Teologi Kebangkitan: Mengkaji Kembali Pemikiran Wolfhart Panenberg Tentang Kebangkitan - Tolop Oloan Marbun (Institut Agama Kristen Negeri Palangka Raya, 2021)
This article examines the theology of resurrection: rethinking the thought of Wolfhart Pannenberg about resurrection. Resurrection is the centre of Pannenberg theology. In his views, the bible should be approached in a historical approach and the resurrection is the climax of incarnation since the incarnation was progressive. The method is a qualitative method with a literature approach. The author will describe Pannenberg’s thought, after that the author will evaluate his thought, and last the author will give argumentations. As the result, histories were written in the bible because of revelation, the resurrection was not the climax of the incarnation. Bible did not agree with the progressive incarnation, and the death of Jesus was not a catastrophe. The conclusion, Bible should be approached in a revelation approach, Jesus as fully God from eternity to eternity. Bible does not have internal testimony that incarnation was progressive. The death of Jesus is penal substitution. Artikel ini membahas tentang Teologi Kebangkitan: Mengkaji ulang pemikiran Wolfhart Pannenberg tentang kebangkitan. Kebangkitan merupakan sentral dari teologi Pannenberg. Dalam pandangan Pannenberg, Alkitab harus dipelajari dengan pendekatan historis dan kebangkitan merupakan klimaks dari inkarnasi. Metode yang digunakan metode kualiatas dengan pendekatan studi Pustaka. Pertama penulis akan deskripsikan pemikiran Pannenberg, selanjutanya penulis akan mengkaji ulang pemikirannya dan terakhir penulis akan memberikan argumentasi. Hasilnya, sejarah ditulis dalam Alkitab karena pewahyuan, kebangkitan bukan klimaks inkarnasi, Alkitab tidak menyetujui inkaranis progresif dan kematian Yesus Kristus bukan sebuah catastrophe. Kesimpulannya, mempelajari Alkitab harus menggunakan pendekatan wahyu, Yesus Kristus adalah Allah dari kekekalan sampai kekekalan, Alkitab tidak memiliki kesaksian internal mengenai inkarnasi progresif, dan kematian Yesus adalah penal substitusi.